Margaret Chase Smith Library 2016 High School Essay Contest: The Ideal Prospective President - Harrington, Elizabeth (Maine Policy Review, 2016)
Each year the Margaret Chase Smith Library sponsors an essay contest for high school seniors. As it was a presidential election year, the 2016 essay prompt asked students to reflect on their ideal candidate for president.